A continuous gas leakage localization method based on an improved beamforming algorithm. (August 2017) - Zhang, Yu; Wang, Jiaqiang; Bian, Xu; Huang, Xinjing; Qi, Lei
Highlights: A method of locating continuous gas leak in both near and far fields is proposed. Measured phase velocity is used to eliminate the frequency dispersion's effects. Experiments demonstrate this method can stably and accurately locate the leak. Abstract: A continuous gas leakage localization method based on an improved beamforming algorithm is proposed and experimentally demonstrated. The ultrasonic signals excited by the leakage are collected by the contact-coupled piezoelectric ultrasonic sensor array, afterward, the time-space matrix of the leakage signal is calculated, and through analyzing the matrix, the position of the leakage hole can be obtained. The measured phase velocity is taken into account in the method to compensate the effect of frequency dispersion. Localization experiments were carried out on a flat plate and a stiffened plate, demonstrating that the proposed method can successfully locate the continuous gas leakage in both the near and far field cases. In addition, the experiment results indicate that frequency dispersion compensation can reduce the localization error efficiently. The method is demonstrated to achieve the mean errors of 3.74 mm and 8.59 mm, for an area of 1 m × 1 m on the flat and stiffened plates, respectively.